Integrating Social Security Benefits with Fintech Retirement Tools - Ajay Benadict Antony Raju (North American Journal of Engineering Research, 2022)
The use of Social Security benefits for introducing precise fintech retirement tools is a rather successful approach to improve the financial outlook for retirees along with the constant development of retirement planning due to technological progress. Social security continues to play a vital role of providing income in retirement, this however, continues to be an area that is often on its own and with management and optimisation not easily tied to other retirement planning. Conventional financial planning, as practiced today, lacks such a holistic view of the individual, and is unable to factor in all the small and big expenses that one might need to save for over the course of his/her working life: fintech solutions present a more accurate means of preparing for post-working years. Incorporating often ill-prepared Social Security benefits with innovative fintech retirement solutions is the focus of this paper and illuminates how I FT forwards the efficient synchronization and optimization of Social Security revenue. Specifically, two attractive features of planning are enabled by the technology: firstly, benefit starting could be recommended depending on personal characteristics; secondly, possibility of the accounts synchronization and optimization of incomes depending on individual conditions is supposed. This inclusion also helps in enhancing a more coherent and coherent procedure for fixing of Social Security regarding planning of retirement benefits and other financial resources. There are gains to be made on this integration that are, increased realism of retirement predictions, increased interactive user participation, and synchronization of benefits with long-term investment plans. Furthermore, some issues that are discussed in the paper include data privacy issues, the problem of compliance with several laws and norms, and the merging of various types of financial data. In dealing with these challenges, incorporation of Social Security benefits with other fintech retirement planning tools constitute a major breakthrough in the future planning for retirees, as many of them, experience a more secure retirement aged planning with a fair chance at a richer ‘Golden age’.